Effects of gamma irradiation on the chemical composition and antioxidant activity of Lactarius deliciosus L. wild edible mushroom - Fernandes, Ângela (2014)
TThe short shelf-life of mushrooms is an obstacle to the distribution and marketing of the fresh product. There has been extensive research on finding the most appropriate technology for mushrooms preservation and a particular interest arises for wild species. Treatment by irradiation emerges as a possible conservation technique that has been tested successfully in several food products. Herein, the effects of gamma irradiation on Lactarius deliciosus (L. ex Fr.) S. F. Gray chemical composition and antioxidant activity were evaluated in samples submitted to different storage periods (0, 4 and 8 days) at 4 °C. The irradiation treatments were performed in a Co-60 experimental equipment. Nutritional value was accessed by macronutrients analysis and determination of energetic value; fatty acid, sugar and tocopherol profiles were determined by gas chromatography– flame ionization detector, high-performance liquid chromatography (HPLC) refractive index and HPLC fluorescence, respectively. The antioxidant activity was evaluated through radical scavenging activity, reducing power, lipid peroxidation inhibition and phenolics content. The obtained data show that, until 1 kGy, gamma irradiation might provide a useful alternative to ensure the quality and extend the life of mushrooms, since its effects on macronutrients, energetic value, tocopherols and antioxidant activity EC50 values were less significant than the changes caused by storage time. Moreover, the chemical and nutritional composition was similar in irradiated and non-irradiated L. deliciosus samples.